Strategic leadership models and theories : Indian perspectives - Sekhar Bhattacharyya, Som; Jha, Sumi (Emerald Publishing Limited, 2018)
Operating in one of the fastest growing economies in the world, Indian business organizations are constantly faced with new challenges. The demands of globalization and the potential disruption of evolving technologies can make effective management difficult. Leadership theories in a business context have been developed mostly by researchers in the West, and very few attempts have been made to theoretically analyse Indian leadership practices. This book explores the idea of an India-centric leadership model, presenting an in-depth research study of strategic leadership theories and applying them to India's unique culture. Using the input of top level Indian business leaders, this book provides a much needed perspective in today's global economy. As one of the first monographs to comprehensively explore Indian leadership practices from an Indian perspective, this book will be of interest to business leaders, researchers and students alike.
Includes index.
Keywords: Leadership -- India -- Methodology.; Business & Economics -- International -- General.; International business.; elektronické knihy; electronic books